2016
DOI: 10.4103/0973-1482.151429
|View full text |Cite
|
Sign up to set email alerts
|

Role of androgen receptor in prostatic neoplasia versus hyperplasia

Abstract: AR nuclear expression is present in benign and malignant prostatic epithelium. In this study, cases of prostate cancer demonstrated a higher staining intensity for AR when compared with BPH. The intensity of AR staining in prostate cancer significantly reduces as the Gleason grade of the tumor increases. The staining intensity for AR was heterogeneous specifically in cases of prostate cancer. Our results indicate that AR maybe considered as a prognostic marker in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…The etiology of benign prostatic hyperplasia (BPH) and prostatic neoplasia, which can progress to PCa, is androgen-dependent, and reduction/obliteration of androgen action in the prostate has been the therapy of choice for BPH and PCa [ 148 ]. A recent study demonstrated that cases of PCa exhibited a higher staining intensity for AR when compared with BPH [ 149 ]. Remarkably, AR is a direct negatively regulated target of p53 [ 150 , 151 ].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of benign prostatic hyperplasia (BPH) and prostatic neoplasia, which can progress to PCa, is androgen-dependent, and reduction/obliteration of androgen action in the prostate has been the therapy of choice for BPH and PCa [ 148 ]. A recent study demonstrated that cases of PCa exhibited a higher staining intensity for AR when compared with BPH [ 149 ]. Remarkably, AR is a direct negatively regulated target of p53 [ 150 , 151 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of an AR low/negative expression pattern has generally been underappreciated, but has been observed in a number of experiments ( Table 2 ). [4] , [5] , [7] , [8] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] More generally, several studies have observed decreased AR protein expression/intensity in hormone-refractory patient metastases, 90 and in hormone-refractory patients when compared to normal, primary, or hormone-sensitive tissue. [86] , [91] CRPC subtypes that exhibit AR low/negative expression patterns (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Higher testosterone levels are associated with smaller prostate size ( Xia et al, 2021 ), and younger age testosterone replacement therapy leads to prostate stabilization ( Zhang Q. et al, 2020 ). In prostate cancer patients, low serum testosterone has been found to be associated with androgen receptor expression ( Schatzl et al, 2002 ; Husain et al, 2016 ; Feng and He, 2019 ; Hashmi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%